Additional records of the pagurid hermit crab genus Trichopagurus de Saint Laurent, 1968 (Crustacea: Decapoda: Anomura), with description of a new species from the Philippines - Komai, Tomoyuki (Zootaxa, 2013)
The pagurid hermit crab genus Trichopagurus de Saint Laurent, 1968 is currently represented by three shallow water spe-cies from the tropical Indo-West Pacific region. In this paper, three species of the genus, including one new species, are reported. Trichopagurus tenuidactylus n. sp. is described on the basis of a single ovigerous female from the Bohol Sea, the Philippines, and compared with two close relatives, T. asper Komai & Poupin, 2012 and T. macrochela Komai & Os-awa, 2005. New locality records are provided for T. macrochela (the Philippines) and T. trichophthalmus (Forest, 1954) (Taiwan and Marianas). An identification key to the four species of the genus is presented.